Laying the foundation for the new doctor of pharmacy degree in the United States - Acosta, Daniel (2000)
In order to understand better the development of the six-year professional doctorate degree in pharmacy, a brief summary of the history of phamacy education in the United States will be provided. In the early 1900's, a two-year diploma from a recognized school of pharmacy was recornmended before a candidate could stand for licensure to practice pharmacy in an individual state. Each state regulates the practice of pharmacy and a state board of pharmacy is responsible for granting a pharmacist the right to practice pharmacy. The board of pharmacy requires a candidate to demonstrate his/her proficiency in pharmacy practice by passing a comprehensive examination in all areas of pharmacy, including the basic pharmaceutical sciences and clínical pharmacy practice. In additíon, the candídate must have a degree in pharmacy from an accredited college of pharmacy. Most states have reciprocal agreements whereby a pharmacist licensed to practice in one state will be allowed to practice nn another state by showing knowledge of state pharmacy laws ín the state to which he/she will be relocating.